2015
DOI: 10.1155/2015/686249
|View full text |Cite
|
Sign up to set email alerts
|

Informational Theory of Aging: The Life Extension Method Based on the Bone Marrow Transplantation

Abstract: The method of lifespan extension that is a practical application of the informational theory of aging is proposed. In this theory, the degradation (error accumulation) of the genetic information in cells is considered a main cause of aging. According to it, our method is based on the transplantation of genetically identical (or similar) stem cells with the lower number of genomic errors to the old recipients. For humans and large mammals, this method can be realized by cryopreservation of their own stem cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Aged bone marrow also decreased growth factor expression, microglia phagocytosis and led to an anxiety/depressive phenotype in young mice. Recent findings have shown that repeated heterochronic bone marrow transplantation without additional conditioning (i.e., irradiation) can extend lifespan by 34% in syngeneic hosts; however, the effects on inflammation, health span and frailty were not addressed [ 40 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aged bone marrow also decreased growth factor expression, microglia phagocytosis and led to an anxiety/depressive phenotype in young mice. Recent findings have shown that repeated heterochronic bone marrow transplantation without additional conditioning (i.e., irradiation) can extend lifespan by 34% in syngeneic hosts; however, the effects on inflammation, health span and frailty were not addressed [ 40 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Probably only human beings realize the inevitable passage of time and the fact of aging and dying. Therefore, since time immemorial people have searched for various life extension methods and rejuvenation strategies which would ensure the longest possible period of youth, fitness, and health (Gavrilov and Gavrilova 1991;Arking 2006;Kwiatkowska and Borysławski 2010;Karnaukhov et al 2015;Kaeberlein and Martin 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This could explain the effective healing by bone marrow (BM) transplantation of not only blood diseases, but also of systemic diseases such as mucopolysaccharidosis, senile hearing loss, and bullous epidermolysis (Birkenmeier et al, 1991; Iwai et al, 2001; Corti et al, 2004; Willenbring et al, 2004; Wagner et al, 2010). We and other authors have shown earlier that radiation-free BM transplantation slows aging (Kamminga et al, 2005; Li et al, 2010; Shen et al, 2011; Kovina et al, 2013; Karnaukhov et al, 2015). Our approach differs from studies of other researchers by the combination of the following parameters (i) larger amount of transplanted material, (ii) close relation of donors and recipients, and (iii) absence of radiation and chemotherapy toxic to the body.…”
Section: Introductionmentioning
confidence: 66%
“…These are lesser risks of infections and of graft-vs.-host disease, threatening to ablated patients, while graft rejection by nonablated recipients is less probable in the elderly than at a younger age because of naturally weaker immune system in the elderly. Even in the absence of histocompatibility, when allogeneic BM was used in a nonablative experiment instead of syngeneic BM, no lifespan shortening of the experimental group was observed (Karnaukhov et al, 2015). Obviously, at an old age the immune system is already too passive to reject donor BM, but it still efficiently suppresses infection and graft-vs.-host reaction, which makes it unnecessary and undesirable to use ablative conditioning in the elderly.…”
Section: Discussionmentioning
confidence: 99%